Circularity in Design Studio: Student Participatory Model in Developing a Paper Recycling System - Az Zahra, Aisyah; Atmodiwirjo, Paramita; Sinuraibhan, Soranart (UI Scholars Hub, 2025)
This study explores the implementation of a participatory model for developing a paper waste recycling system and integrating it within architectural design education. In response to the high level of paper waste inherent in design studio learning, the initiative treats waste not as a final output but as reusable material for further resources. A student-led, participatory model was established to design and implement a paper waste recycling system, including the establishment of a sorting hub in the studio environment, regular waste tracking, and hands-on workshops on various forms of paper reuse and recycling. The process evolved through regular feedback, peer coordination, and internal reflection, eventually forming a self-sustaining initiative. Evaluation methods included surveys, interviews, and visual documentation throughout the process. Framing design learning as both a material and behavioral practice, this study contributes a model with potential replication for embedding circular practices into higher education, particularly in resource-intensive creative disciplines.